PERSPEKTIF KARYAWAN DALAM PENELITIAN MANAJEMEN BAKAT: TINJAUAN LITERATUR - Hardy, Human; Afrianty, Tri Wulida; Prasetya, Arik (PROFIT: JURNAL ADMINISTRASI BISNIS, 2020)
Research on the employee perspective of talent management is scarce. The focus of this literature review is to specifically consider the employee in talent management. The purpose of this literature review is threefold. First, this literature review presents a review of the existing talent management literature broadly, in order to present a synthesis of what is known and what is not known. Second, this literature review then sharpens the focus of the review to present a review of the literature which specifically acknowledges the employee perspectives within talent management. Third, this literature review presents a future direction regarding employee perspective within talent management. This literature review used the systematic approach to the review. The final sample of 208 scholarly papers for review which includes empirical papers among the other conceptual work, reviews and book chapters of which only 24 considered the employee perspective. This literature review has identified that, while the literature has recently acknowledged the employee as a central participant and central actor in organizational strategic talent management, both conceptual and empirical work in this stream is as yet highly limited and requires substantial further conceptual and empirical development.